1996
DOI: 10.1159/000266408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acoustical, Visual and Tactile Echo on Speech Fluency of Stutterers

Abstract: The study presents the comparison of the effects of echo transmitted via single and combined channels (auditory, visual and tactile) on the speech of stutterers. The dependence of stuttering intensity and speech velocity upon echo delay time was determined. For all transmission channels the stuttering intensities and the speech velocities decreased with the increase in the delay time of the echo. The results were analyzed statistically by means of the ANOVA method. It was proven that the corrective effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…Further, these signals can be endogenously produced by a second source (for example, choral speech, shadowed speech, and masking auditory feedback (MAF)) (Kalinowski et al 1993, 2000, Cherry and Sayers 1956) or endogenously triggered such that it is dependent on one's own speech output (for example, delayed auditory feedback (DAF), and frequency‐altered feedback (FAF)) (Bloodstein and Bernstein‐Ratner 2008, Kalinowski and Dayalu 2002, Keifte and Armson 2006, Kuniszyk‐Jozkowiak and Adamczyk 1989, Kuniszyk‐Jozkowiak et al 1996, 1997, Silverman 1996, Smolka and Adamczyk 1992, van Riper 1971, Yates 1963). Finally, these second signals can be delivered via the auditory (for example, DAF, masking, and reverberation; Kalinowski et al 1993, Lincoln et al 2006), visual (for example, visual choral speech (VCS), and lights with varying on/off frequency durations; Kalinowski et al 2000, Kuniszyk‐Jozkowiak and Adamczyk 1989, Smolka and Adamczyk 1992, Snyder et al 2009), or tactile modality (for example, tactile sensors placed on the fingertips; Kuniszyk‐Jozkowiak and Adamczyk 1989, Kuniszyk‐Jozkowiak et al 1996, 1997). Overall, it should be noted that the modality of the signals and signal characteristics influences the extent of stuttering frequency reduction with auditory choral speech being the most potent signal in reducing stuttering.…”
Section: Introductionmentioning
confidence: 99%
“…Further, these signals can be endogenously produced by a second source (for example, choral speech, shadowed speech, and masking auditory feedback (MAF)) (Kalinowski et al 1993, 2000, Cherry and Sayers 1956) or endogenously triggered such that it is dependent on one's own speech output (for example, delayed auditory feedback (DAF), and frequency‐altered feedback (FAF)) (Bloodstein and Bernstein‐Ratner 2008, Kalinowski and Dayalu 2002, Keifte and Armson 2006, Kuniszyk‐Jozkowiak and Adamczyk 1989, Kuniszyk‐Jozkowiak et al 1996, 1997, Silverman 1996, Smolka and Adamczyk 1992, van Riper 1971, Yates 1963). Finally, these second signals can be delivered via the auditory (for example, DAF, masking, and reverberation; Kalinowski et al 1993, Lincoln et al 2006), visual (for example, visual choral speech (VCS), and lights with varying on/off frequency durations; Kalinowski et al 2000, Kuniszyk‐Jozkowiak and Adamczyk 1989, Smolka and Adamczyk 1992, Snyder et al 2009), or tactile modality (for example, tactile sensors placed on the fingertips; Kuniszyk‐Jozkowiak and Adamczyk 1989, Kuniszyk‐Jozkowiak et al 1996, 1997). Overall, it should be noted that the modality of the signals and signal characteristics influences the extent of stuttering frequency reduction with auditory choral speech being the most potent signal in reducing stuttering.…”
Section: Introductionmentioning
confidence: 99%
“…Findings demonstrating the integration of auditory and visual information during speech perception [5,6,[12][13][14]20] Previous research has reported that visual feedback [10,11,17] in the form of a flashing light reduces stuttering frequency, however, not as impressively as observer with VCS. It would appear that sensory feedback that is congruous to the speech production in the stutterer is the most Fluent Speech Via Visual Choral Speech 7 ameliorative toward reducing stuttering.…”
mentioning
confidence: 99%
“…This notion is supported by the fact other forms of auditory feedback (e.g., masked auditory feedback, metronome, etc.) [1,7] and feedback in the tactile modality are not as effective [9][10][11]17] as AAF and VCS.…”
mentioning
confidence: 99%
“…VTF could not access the synchrony-detection mechanism since vibration is not transmitted via the cerebellum. Nevertheless, VTF improves the fluency of PWS (Kuniszyk-Jozkowiak et al, 1996;Snyder et al, 2009;Waddell et al, 2012). This suggests that rate control by the cerebellum is not the only way to improve fluency.…”
Section: Model For Processing Auditory Inputs That Are Asynchronous Wmentioning
confidence: 96%
“…In contrast, any cerebellar mechanisms involved in fluency-enhancement could only be accessed by auditory inputs because they transmit to this structure whereas vibrotactile stimulation by-passes them. Kuniszyk-Jozkowiak et al (1996) investigated how synchronous and asynchronous auditory, vibratory and visual speech feedback affected fluency (percentage syllables stuttered, %SS) and speaking rate (number of syllables uttered per second). Synchronous (0 ms delay) and asynchronous (delays of 50, 100 and 160 ms) feedback were investigated in all modalities.…”
Section: Introductionmentioning
confidence: 99%